Analisis Preferensi Mahasiswa Terhadap Penggunaan BNI Mobile Banking : Studi Kasus Mahasiswa Ekonomi Pembangunan Universitas Katolik Widya Mandira - Kharina Lidia Priskalina Oil; Novi Theresia Kiak; Fransina W. Ballo (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the preferences of Development economics students at Widya Mandira Catholic University towards using BNI mobile banking and to determine the preference factors for using mobile banking for Development economics students at Widya Mandira Catholic University. The data used in this research are primary and secondary data, which were then analyzed using qualitative descriptive analysis methods. The data collection techniques used in this research used interview, observation and documentation techniques. The results of this research show that the preference or interest of Development Economics students at Widya Mandira Catholic University, Kupang City in using Mobile banking is still small or minimal, especially in UKT payments. Most students are more interested in making payments via BNI Bank directly rather than using Mobile banking. There are several factors that cause preference in using Mobile banking for Development Economics students at Widya Mandira Catholic University, namely internal factors such as lifestyle needs, culture/habits and beliefs. Meanwhile, external factors such as service availability, environment/situation, and security.